Can Nebulised Colistin Therapy Improve Outcomes in Critically Ill Children with Multi-Drug Resistant Gram-Negative Bacterial Pneumonia? - Fatih Aygun; Fatma Deniz Aygun; Fatih Varol; Cansu Durak; Haluk Cokugraş; Yildiz Camcioglu; Halit Cam (MDPI AG, 2019)
In the past decade, multidrug-resistant (MDR) gram-negative bacteria have become a major problem, especially for patients in intensive care units. Recently, colistin became the last resort therapy for MDR gram-negative bacteria infections. However, nebulised colistin use was limited to adult patients. Thus, we investigated the efficacy and safety of nebulised colistin treatment against MDR microorganisms in the paediatric intensive care unit (PICU). Data of all patients admitted for various critical illnesses (January 2016 to January 2019) were reviewed. Differences between groups (with and without a history of nebulised colistin) were compared. Of 330 patients, 23 (6.97%) used nebulised colistin. Significant relationships were found between nebulised colistin usage and several prognostic factors (inotropic drug use (p = 0.009), non-invasive mechanical ventilation (p ≤ 0.001), duration in PICU (p ≤ 0.001), and C-reactive protein level (p = 0.003)). The most common microorganism in tracheal aspirate and sputum cultures was Pseudomonas aeruginosa (13 patients). The most common underlying diagnosis was cystic fibrosis, noted in 6 patients. No serious nephrotoxicity and neurotoxicity occurred. This study showed that colistin can be safely used directly in the airway of critically ill children. However, nebulised colistin use did not have a positive effect on mortality and prognosis.